Somatotopy and Organization of Spinothalamic Tracts in the Human Cervical Spinal Cord. Issue 6 (13th July 2018) - Vedantam, Aditya; Bruera, Eduardo; Hess, Kenneth R; Dougherty, Patrick M; Viswanathan, Ashwin
Abstract: BACKGROUND: Understanding spinothalamic tract anatomy may improve lesioning and outcomes in patients undergoing percutaneous cordotomy. OBJECTIVE: To investigate somatotopy and anatomical organization of spinothalamic tracts in the human cervical spinal cord. METHODS: Patients with intractable cancer pain undergoing cordotomy underwent preoperative and postoperative quantitative sensory testing for sharp pain and heat pain on day 1 and 7 after cordotomy. Intraoperative sensory stimulation was performed with computed tomography (CT) imaging to confirm the location of the radiofrequency electrode during cordotomy. Postoperative magnetic resonance (MR) imaging was performed to define the location of the lesion. RESULTS: Twelve patients were studied, and intraoperative sensory stimulation combined with CT imaging revealed a somatotopy where fibers from the legs were posterolateral to fibers from the hand. Sharpness detection thresholds were significantly elevated in the area of maximum pain on postoperative day 1 ( P  = .01). Heat pain thresholds for all areas were not elevated significantly on postoperative day 1, or postoperative day 7. MR imaging confirmed that the cordotomy lesion was in the anterolateral quadrant, and in this location the lesion had a sustained effect on sharp pain but a transient impact on heat pain. CONCLUSION: In the high cervical spinal cord, spinothalamic fibers mediating sharp pain for the arms are located ventromedial to fibers for the legs, and these fibers are spatially distinct from fibers that mediate heat pain.